Stepwise reprogramming of liver cells to a pancreas progenitor state by the transcriptional regulator Tgif2 - Nuria Cerdá-Esteban (Nature Portfolio, 2017)
Liver and pancreas cells arise from a common endoderm progenitor in the embryo, but what regulates their cell fate is unclear. Here, the authors show that expression of the Three-Amino-acid-Loop-Extension (TALE) homeobox TG-interacting factor 2 (TGIF2) in hepatocytes reprogrammes the cells to a pancreatic fate.